Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1088/1475-7516/2017/10/010
|View full text |Cite
|
Sign up to set email alerts
|

Stellar recipes for axion hunters

Abstract: Abstract. There are a number of observational hints from astrophysics which point to the existence of stellar energy losses beyond the ones accounted for by neutrino emission. These excessive energy losses may be explained by the existence of a new sub-keV mass pseudoscalar Nambu-Goldstone boson with tiny couplings to photons, electrons, and nucleons. An attractive possibility is to identify this particle with the axion -the hypothetical pseudo Nambu-Goldstone boson predicted by the Peccei-Quinn solution to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
373
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 258 publications
(394 citation statements)
references
References 171 publications
(332 reference statements)
18
373
0
3
Order By: Relevance
“…figure 12. Intriguingly, for m A = O(10) meV and tan β 0.3, the axion in this model may explain at the same time recently observed stellar cooling excesses observed from helium burning stars, red giants and white dwarfs [77].…”
Section: Jhep02(2018)103supporting
confidence: 67%
See 2 more Smart Citations
“…figure 12. Intriguingly, for m A = O(10) meV and tan β 0.3, the axion in this model may explain at the same time recently observed stellar cooling excesses observed from helium burning stars, red giants and white dwarfs [77].…”
Section: Jhep02(2018)103supporting
confidence: 67%
“…Note that the region in the N DW = 3 case has been derived under the assumption that the PQ symmetry is protected by a discrete symmetry, so that Planck scale suppressed PQ violating operators are allowed at dimension 10 or higher [69]. In the last two lines the projected sensitivities of various experiments are indicated [70][71][72][73][74][75][76][77].…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As evident from the figure, the SN bound is competitive with the RGB bound, however not dominating, except for low values of tan β. When compared with the expected IAXO potential [9,20], it is evident that helioscopes of the next generation have the capability to explore large regions of the axion parameter space that are not affected by the SN analysis. As stressed above, the results of our analysis should not be considered as a robust bound as we are not including the axion feedback on the star, which at these couplings is most likely non-negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Axions with the properties described here not only would perturb the cooling of white dwarfs but they would also modify in a subtle way the evolution of other kind of stars. An extensive review can be found in Giannotti et al, (2017), while Sedrakian (2019) provides a recent analysis of the cooling by DFSZ axions of the neutron star in Cas A. Here only the two more restrictive tests are presented.…”
Section: Discussionmentioning
confidence: 99%